A Case of Excavated Pneumopathy after Bronchial Thermoplasty - M, Steger; N, Migueres; N, Khayath; C, Marcot; C, Matau; F, Arboit; M, Ohana; F, De Blay (Archives of Clinical and Medical Case Reports, 2022)
Bronchial thermoplasty (BT) is a bronchoscopic treatment for patients with severe asthma that remains uncontrolled despite optimal medical therapy. Several adverse effects and acute radiological abnormalities have been described, but excavated pneumopathy has never been reported as a complication of BT. We describe the development of excavated pneumopathy after the last BT procedure. A 60-year-old woman with severe uncontrolled asthma, despite maximal medical treatment, underwent BT. After the third procedure, she developed an exacerbation of asthma with respiratory deterioration after a reduction in systemic corticosteroid treatment. Chest computer tomography revealed nodular excavated opacities in contact with the bronchial tree, limited to the upper lobes and the lingula. This case suggested that intense thermal stimulation of the bronchial mucosa may lead to tissue fragility and alveolar lung lesions.